Teaching toWard democracy : educators as agents of change - Ayers, William; Kumashiro, Kevin K., 1970-; Meiners, Erica R.; Quinn, Therese; Stovall, David (Routledge, an imprint of Taylor and Francis, 2015)
"Teaching Toward Democracy" examines the contested space of schooling and school reform with a focus on the unique challenges and opportunities that teaching in a democratic society provides. Teaching in and for democracy involves developing particular qualities of mind that teachers explore and work to develop as they become more effective educators. Some chapters open with familiar experiences in the lives of teachers in schools (working with parents and communities, or dealing with classroom discipline and management) and illuminate that commonplace in new, helpful, and sometimes startling, ways. Other chapters present possible interventions any teacher might make in any classroom for example, using the arts as an organizing center and metaphor for teaching more generally, or rethinking the press of politics on our every day practice. This book foregrounds the central idea that democratic ideals are a necessary starting point and context in which to enact our teaching here and now."
Keywords: Citizenship -- Study and teaching -- United States.; Teaching -- Social aspects -- United States.; Democracy and education -- United States.; Social change -- United States.; Citoyenneté -- Étude et enseignement -- États-Unis.; Démocratie et éducation -- États-Unis.; EDUCATION -- Essays.; EDUCATION -- Organizations & Institutions.; EDUCATION -- Reference.; Citizenship -- Study and teaching; Democracy and education; Social change; Teaching -- Social aspects; United States